Development and assessment of a biomass-gasification based multigenerational plant for production of hydrogen and ammonia fuels - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim (ELSEVIER SCI LTD, 2025)
Due to increased levels of local and global environmental concerns and energy problems, there is a strong need for alternative, clean, safe and cheap energy sources. Besides, there is an additional need that energy sources should be treated more efficiently and effectively. This may include optimizing energy conversion processes to maximize useful outputs and minimize losses, improving storage capacities to ensure a reliable and continuous supply, and integrating resilient grid systems to manage distribution more effectively. Advances in energy efficiency also involve developing materials and technologies that enhance the performance of renewable energy systems, such as high-efficiency solar panels, advanced wind turbine designs, and more efficient biomass conversion techniques. Biomass has been selected as a unique energy source for the present integrated energy plant. Likewise, an efficient plant type, multigeneration, is offered for biomass sources. This work uses a new biomass gasification-based multigenerational plant for power, hydrogen, ammonia, fresh water, and cooling production. The biomass gasification system, Brayton plant, Rankine cycle, freshwater production plant, hydrogen production and storage system, ammonia production system, Kalina plant, and single-effect absorption cooling system are integrated effectively to achieve these goals. Unlike previous studies, the present biomass-gasification-based multigeneration system proposed in this research stands out in terms of its components and products. The system is thoroughly examined through thermodynamic and economic analyses, as well as parametric investigations. To validate the study's findings, some comparisons are made with the study results drawn from the relevant literature. The results reveal that both energetic and exergetic analyses of the multigeneration plant yield efficiencies of 70.92% energetically and 68.87 % exergetically. The overall exergy destruction rate of the proposed system is calculated as 28143 kW, underscoring the novelty and potential of this innovative approach.
Keywords: Biomass; Multigeneration plant; Renewable energy; Hydrogen; Ammonia; Exergy; Fuel; EXERGY ANALYSIS; ENERGY; POWER; SYSTEM; CYCLE; ELECTROLYZER; OPTIMIZATION; DESALINATION; PERFORMANCE; Energy & Fuels; Engineering